Himig ng kabataan a module on ukulele and rondalla playing for San Francisco High School Grade 7 Special Program in the Arts-Music - Basug, Arnida Faye
At the end of the project, the Special Program in the Arts or SPA of the San Francisco High School (SFHS) is a program made to allow telented students enhance their potential in different aspects in arts. There are five different fields to choose from: Creative Writing in Filipino and English; Visual Arts; Theater Arts; Music; and Dance. The SPA music curriculum focuses on aspects such as: "Music as self-expressed in FIlipino tales, epics, rituals and festivals; music as a community resource in the ritual's tangible and intangible heritage of the people; music as continuing expression of the people's history and music as a global perspective in the contemporary times.